PROSES PEMBUATAN MINUMAN ANGGUR DAGING BUAH PALA DENGAN JENIS DAN KOSENTRASI STARTER RAGI YANG BERBEDA [Wine Making Process Meat Fruit Nutmeg with type and concentration of Different Yeast stater] - Wijayanti, Fitri Wahyu; Ijong, F. G.; Mandey, L. C (Jurnal Ilmu dan Teknologi Pangan, 2013)
A research on processing of wine nutmeg meat was done usingÂ  some yeast as a starter and the fermentation was held at room temperature for 14 days. The aim of current research were to analyze total sugar, total acid, and pH during fermentation process. Research methods using completely randomized design with treatment on the type (Saccharomyces cerevisiae, Amylomyces rouxii, and Rhizopus oligosporus) with concentrations (4, 6, 8 grams). The results show that the best wine meat nutmeg obtained by using Rhizopus oligosporus treatment at a concentration of 4 grams with the following characteristics of total sugar 1.15% total acid 0.19% and pH 3.28. Further more the organoleptic taste and odohedonic quality value were like and rather likes to color on the concentration of 8 grams.